Nurses' willingness to work with COVID‐19 patients: The role of knowledge and attitude - Abdulqadir J. Nashwan; Ahmad A. Abujaber; Ahmed S. Mohamed; Ralph C. Villar; Mahmood M. Al‐Jabry (Wiley, 2021)
Abstract Aim This study aims to assess the role of nurses' knowledge and attitude in relation to their willingness to work with patients diagnosed with COVID‐19 in Qatar. Design A cross‐sectional study. Methods A self‐administered, 35‐item online survey was circulated to the Registered Nurses working in Hamad Medical Corporation, the principal healthcare provider in Qatar. Results A total of 580 attempts to complete the survey. Of them, 377 completed surveys with a response rate of 65%. Logistic regression was used to predict nurses' willingness to work with patients with COVID‐19. Nurses' knowledge level and monetary compensation that is associated with the work‐environment risk category were found to have a significant positive relationship with the nurses' willingness to care for patients with COVID‐19 (p < .05). The findings of this study may help nursing leaders design educational programmes and remuneration models that may help boost nurses' willingness to work with high‐risk patient groups, especially during a pandemic.